Comparing the Impact of Wind Power and Solar Power Investment on Industrial Development: Application of Dynamic Energy Industry-related Models - Hong, Cheng-Yih; Chang, Hsiu-Ching (International Journal of Energy Economics and Policy, 2019)
Taiwan’s energy transformation to change the power structure is a new energy policy for economic development, industrial upgrading and environmental preservation. This study investigates the possibility of evaluating the economic spillover effects and CO2 emissions to evaluate new energy policy objectives by investing in solar and wind power generation systems. The research results show that the short-term solar investment in economic effects is superior to wind power generation, and the economic spillover increases the scale of CO2 emissions. The main reason is that the high ratio of equipment for wind power generation comes from imports and reduces the spillover effect. Observing the economic spillover effects of individual industries, solar investment has the largest increase in “Sewage Treatment Sector and Resource Recovery” sectors, while wind investment has the largest increase in “Machinery-related industries”. The scale of CO2 emissions in individual industries, solar investment has increased the most emissions by “Chemical” sectors, and wind investment has increased by “Service industries”. However, from a long-term perspective, the industrial upgrading through economic restructuring and the low emission coefficient of wind power will greatly improve the economic spillover effect of wind investment and improve the environment. Keywords: solar power, wind power, economic spillover effects, CO2 emissions. JEL Classifications: Q43, Q56, C54, C67 DOI: https://doi.org/10.32479/ijeep.8152